THE ROLE OF INFORMATION TECHNOLOGY IN MALAYSIA’S DIGITAL EDUCATION POST-PANDEMIC - M. Khairi Mahyudin; Sam Hermansyah (CV. Fahr Publishing, 2025)
This study explores the evolving role of digital technology in Malaysia’s education system in the aftermath of the COVID-19 pandemic. The primary objective is to assess how information and communication technologies (ICT) have been integrated into teaching and learning practices across different educational levels, and to evaluate the effectiveness, challenges, and equity implications of digital transformation in Malaysian schools. Employing a qualitative research approach through a systematic literature review (SLR), this study synthesizes findings from recent academic research, policy documents, and empirical reports published between 2020 and 2025. Data were analyzed using thematic content analysis to identify patterns related to access, pedagogy, institutional readiness, and policy direction. The findings reveal that while Malaysia has made significant strides in digital infrastructure development and teacher ICT readiness, issues such as the digital divide, unequal access in rural areas, and gaps in digital pedagogy persist. Teachers generally report increased digital competency, but many still face challenges in implementing student-centered, technology-enhanced instruction due to limited resources and institutional support. Leadership and policy alignment play a critical role in the success or stagnation of digital initiatives. The novelty of this study lies in its integrated, multi-level analysis of Malaysia’s digital education transformation, incorporating recent developments in leadership, AI integration, and equity-focused policy. It offers a forward-looking perspective on building a sustainable, inclusive digital learning ecosystem. The study concludes that meaningful progress depends not only on technology availability but also on systemic reforms that prioritize equity, innovation, and capacity building at all levels of education.